Französische Einflüsse im Bilde der Kulturlandschaft Nordamerikas: Hufensiedlungen und Marschpolder in Kanada und in Louisiana - Bartz, Fritz (ERDKUNDE, 1955)
During the 117th and 18th centuries French colonists and their descendants established in the region of the lower St. Lawrence and some of its tributaries a type of rural settlement which resembles in many ways the „Hufen-villages of Europe. Traces of this arrangement of the holdings in „long lots are also found in certain parts of the American and Canadian Middle West and especially also in the delta region of the Mississippi, where settlers of French mother tongue can still be found. Though this type of settlement has been modified during the centuries in Quebec Province it is still preserved to this day. The problem of the origin of this long lot settlement is still unsolved. In contrast, it is quite obvious that the stimulus for impoldering small areas of coastal marsh around Fundy Bay was due to Old World -influences. During the recent past these polder regions have been rather neglected, but at present the state is taking action to help them to regain a more important economic position.